Influencing factors on sustainability reporting quality based on sustainable development goals (SDGS) considering COVID-19 - Idawati, Wiwi; Prabowo, Hayu S.; Pratiwi, Anneta Rizki; Simatupang, Batara Maju (Business: Theory and Practice, 2024)
In 2020, the major companies in the Asia Pacific region faced challenges in sustainability performance reporting, primarily attributed to disruptions caused by the COVID-19 pandemic. This crisis compelled companies to reassess their sustainability goals. This study aims to analyze the relationship between corporate governance and corporate characteristics such as industry type and government ownership of sustainability reporting quality based on sustainable development goals (SDGs) with a population of 200 companies in ASEAN countries, including Indonesia, Malaysia, Thailand, and the Philippines, listed on each country’s stock exchange. The research sample consisted of 84 companies selected through purposive sampling. The hypothesis testing model employed a multiple linear regression method and utilized the panel data regression analysis approach. The findings indicate that the three corporate governance components examined in this research board independence, audit committee, and managerial ownership, along with government ownership do not exert a significant influence on sustainability reporting quality based on the seventeen SDGs goals. Furthermore, we believe that this research is very important to be carried out in Indonesia, given that environmentally sensitive industries face the risk of environmental damage and therefore need legitimacy to maintain their operations, demonstrated through sustainability report reporting.